2016
DOI: 10.1371/journal.pone.0148560
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle Disease Virus V Protein Targets Phosphorylated STAT1 to Block IFN-I Signaling

Abstract: Newcastle disease virus (NDV) V protein is considered as an effector for IFN antagonism, however, the mechanism remains unknown. In this study, the expression of STAT1 and phospho-STAT1 in cells infected with NDV or transfected with V protein-expressing plasmids were analyzed. Our results showed that NDV V protein targets phospho-STAT1 reduction in the cells depends on the stimulation of IFN-α. In addition, a V-deficient genotype VII recombinant NDV strain rZJ1-VS was constructed using reverse genetic techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 55 publications
1
38
0
Order By: Relevance
“…and differentiation, as well as antiviral responses. The expressions of a diverse subset of genes identified in this study are in agreement to the previously reported literature where a moderate antiviral functionality is observed against NDV [12,49,50]. Moreover, chIFN-γ is unique in its functionality in the cascade of pathogenic attack against host cells, because it is significantly active in creating an overall antiviral environment against invading pathogens.…”
Section: The Pattern Of Gene Expression Post-chifn-γ Treatmentsupporting
confidence: 90%
“…and differentiation, as well as antiviral responses. The expressions of a diverse subset of genes identified in this study are in agreement to the previously reported literature where a moderate antiviral functionality is observed against NDV [12,49,50]. Moreover, chIFN-γ is unique in its functionality in the cascade of pathogenic attack against host cells, because it is significantly active in creating an overall antiviral environment against invading pathogens.…”
Section: The Pattern Of Gene Expression Post-chifn-γ Treatmentsupporting
confidence: 90%
“…We and others previously reported that NDV V protein can inhibit RLR-mediated interferon signaling by targeting MDA-5, LGP2, STAT1, etc. (22,(25)(26)(27). In this study, we provided several lines of evidence to demonstrate that NDV V protein targets MAVS degradation and subsequently inhibits RLR signaling to benefit virus proliferation at late stages.…”
Section: Discussionmentioning
confidence: 91%
“…To our surprise, in both WT and MAVS Ϫ/Ϫ 293T cells, the virus titers in the supernatant of NDV-infected cells were higher than those in ΔV ZJ1-infected cells. Since paramyxovirus V protein could target several other RLR signaling pathway-related molecules, including MDA5, LGP2, and STAT1, and inhibit the IFN-␤ signaling pathway (25)(26)(27), knockout of MAVS alone is not sufficient to cover the effect of V deletion. However, interestingly, the finding that MAVS knockout significantly increased virus infection in NDV but not the ΔV ZJ1 infection group suggests NDV V protein is necessary for specifically antagonizing MAVS-mediated innate immunity and virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…11,150 Studies using reverse genetics have also identified the viral replication complex (N, P and L proteins) as influencing the pathogenicity of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…The V protein may also contribute to the virulence of NDV, by modulating the innate immune response of the host and acting as an alpha interferon antagonist. 10,149,150 In one study, mutations introduced into the V protein of recombinant ND viruses were found to attenuate the virus and decrease the virulence of the viruses in embryonated eggs. 151 A further study supported this theory and found that viruses with mutations in the V protein were attenuated in-vivo.…”
Section: Proteinmentioning
confidence: 99%